Factors associated with gerontological nursing practice among nurses in comprehensive nursing care service units: A cross-sectional descriptive study - Hye Bin Park; So Young Shin (Journal of Korean Gerontological Nursing, 2026)
Purpose: In comprehensive nursing care service units (CNCSUs), where family caregivers are rarely present, nurses are primarily responsible for both medical treatment and daily care, making professional gerontological nursing practice essential. This study investigated factors associated with gerontological nursing practice among nurses in CNCSUs. Methods: A cross-sectional descriptive study was conducted. The participants included 153 nurses at two general hospitals in Korea. A structured self-reported questionnaire was administered to assess general characteristics, perceived patient safety culture, moral sensitivity, organizational communication satisfaction, and gerontological nursing practice. Data were analyzed using descriptive statistics, t-tests, one-way ANOVA, Pearson correlation coefficients, and multiple linear regression. Results: The 153 participants had a mean age of 29.32 years. In the multiple regression analysis, the factors associated with gerontological nursing practice of subjects included perceived patient safety culture (β=.23, p=.004), experience volunteering with older adults (β=.20, p=.008), moral sensitivity (β=.20, p=.009), and organizational communication satisfaction (β=.16, p=.046). The regression model explained 29.0% of the variance in gerontological nursing practice (F=7.78, p